Interactions of neural-like cells with 3D-printed polycaprolactone with different inner diameters for neural regeneration - Zolzaya Javkhlan; Sheng-Hao Hsu; Rung-Shu Chen; Min-Huey Chen (Elsevier, 2024)
Background/purpose: Peripheral neural regeneration is an interesting and challenging field. The aim of this study was to investigate the interactions of neural-like PC12 cells and Poly-D-Lysine (PDL)-coated 3D-printed polycaprolactone (PCL) scaffolds with different inner diameters of half tubular array (HTA) (0, 200, 300, and 400 μm), respectively. Materials and methods: This study used the fused deposition modeling (FDM) technique with 3D-printing to fabricate the thermoplastic polymer. Scaffold properties were measured by mechanical testing, and coating quality was observed under a scanning electron microscope (SEM). PC12 cell biocompatibility was examined by an MTT assay. Cell differentiation was evaluated by immunofluorescence staining. Results: The cell viability of PC12 cells on PDL-coated PCL scaffolds with a 200-μm inner diameter of HTA was shown with significant differences (∗P < 0.05, ∗∗P < 0.01, ∗∗∗P < 0.001) than other PCL groups at all experimental dates. The SEM observation showed that PDL-coated PCL scaffolds with 200-μm inner diameters of HTA promoted cell adhesion. An immunofluorescence staining of PC12 cells on the PDL-coated PCL scaffold with a 200-μm inner diameter of the HTA group showed that it stimulated PC12 cells for neurite formation much better than the other groups.A PDL-coated PCL scaffold with a 200-μm inner diameter of HTA can promote the growth and differentiation of PC12 cells better than other groups. It indicated that PDL-coated PCL scaffolds with a 200-μm inner diameter HTA can be used for further neural regeneration application.